Comparative Study Between Therapeutic Effects of Melatonin and Zinc in Lead induced Toxicity in Rats - Mustafa Ghazi Alabbassi; Mustafa M. Ibraheem; Mohammed A. Ibrahim (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2010)
The present study was designed to investigate the therapeutic effects of melatonin as well as zinc in combination or each one alone against the hepatic and renal toxicity of lead in male rats. Five groups of animals were allocated as follows: Group I, includes 12 rats injected subcutaneously with 0.2 ml physiological saline for 60 days; groups II and III, each includes 12 rats, injected with lead acetate 100 mg/kg/day s.c for 30 days, followed by treatment with intraperotoneal injection of physiological saline (0.2 ml) or melatonin 30mg/kg/day for the next 30 days. Group IV, include 12 rats, injected with lead acetate 100 mg/kg/day s.c for 30 days, followed by treatment with intraperotoneal injection of zinc sulphate 1.5 mg/kg/day for the next 30 days. Group V, includes 12 rats injected with 100mg/kg lead acetate s.c for 30 days followed by treatment with intraperitoneal injection of 30 mg/kg/day melatonin and 1.5mg/kg/day zinc sulphate for the latter 30 days. At the end of treatment period, the rats were sacrificed by an overdose (100mg/kg) of thiopental (twenty-four hour after the last injection). Laparotomies were performed to obtain the livers and kidneys for the assessment of tissue damage. Oxidative stress parameter (MDA), hemoglobin content, liver and renal functions, and histological appearance of the studied organs were evaluated and compared with that of negative and positive controls. Treatment with melatonin or zinc reverses the damage induced by lead in many organs and tissues through the reduction of MDA levels in RBCs, liver and kidneys; in addition to the improvement in the indices of the functions of the organs studied. These findings demonstrated that addition of zinc to melatonin are capable of further reversing damage of rat tissues caused by successive doses of lead acetate, and animals had restored their organ functions due to combined treatment.